The Eighth Grade Students' Vocabulary Mastery and Writing Descriptive Text Ability - Purnomo, Hari Agus; Irawan, Candra; Pratama, Dedy (CV. Doki Course and Training, 2023)
The purposes of this research were to find out the correlation between students’ vocabulary mastery and writing descriptive text and the contribution of vocabulary mastery on writing ability. The population of the study was all of the 8th grade students in SMP Negeri 6 Lempuing. In choosing the sample, random sampling was used that involved 134 students. The data were collected by using vocabulary mastery and writing descriptive text ability tests. The data were analyzed by using Pearson Product Moment to investigate the correlation between both variables and regression analysis. The results showed that the coefficient of R-value was 0.557. The category of correlation between vocabulary mastery and writing ability showed a moderate correlation. It was found that there was significant correlation between students’ vocabulary mastery and writing descriptive text ability of the eighth-grade students in SMP Negeri 6 Lempuing. There was also contribution of vocabulary mastery to writing descriptive text ability of the eighth-grade students as much 31%. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. In other words, having a rich vocabulary mastery can make students easier for students to write especially for writing descriptive text.